What equation is equivalent to 6x + 13 – (3x – 7)

Question

What equation is equivalent to 6x + 13 – (3x – 7)

in progress 0
Tài Đức 5 months 2021-08-26T00:57:23+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-26T00:58:41+00:00

    Answer:

    6x + 12 – (3x – 7)

    6x + 12 – 3x + 7

    3x + 19

    0
    2021-08-26T00:58:42+00:00

    Step-by-step explanation:

    Simplifying

    6x + 13 + -3x + -7 = 0

    Reorder the terms:

    13 + -7 + 6x + -3x = 0

    Combine like terms: 13 + -7 = 6

    6 + 6x + -3x = 0

    Combine like terms: 6x + -3x = 3x

    6 + 3x = 0

    Solving

    6 + 3x = 0

    Solving for variable ‘x’.

    Move all terms containing x to the left, all other terms to the right.

    Add ‘-6’ to each side of the equation.

    6 + -6 + 3x = 0 + -6

    Combine like terms: 6 + -6 = 0

    0 + 3x = 0 + -6

    3x = 0 + -6

    Combine like terms: 0 + -6 = -6

    3x = -6

    Divide each side by ‘3’.

    x = -2

    Simplifying

    x = -2

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )